Effects of golf shaft stiffness on strain, clubhead presentation and wrist kinematics - Betzler, N. F.; Monk, S. A.; Wallace, E. S.; Otto, S. R. (Sports Biomechanics, 2012)
The aim of this study was to quantify and explain the effect of shaft stiffness on the dynamics of golf drives. Twenty golfers performed swings with two clubs designed to differ only in shaft bending stiffness. Wrist kinematics and clubhead presentation to the ball were determined using optical motion capture systems in conjunction with a radar device for capturing ball speed, launch angle, and spin. Shaft stiffness had a marginally small effect on clubhead and ball speeds, which increased by 0.45% (p < 0.001) and 0.7% (p = 0.008), respectively, for the less stiff club. Two factors directly contributed to these increases: (i) a faster recovery of the lower flex shaft from lag to lead bending just before impact (p < 0.001); and (ii) an increase of 0.4% in angular velocity of the grip of the lower flex club at impact (p = 0.003). Unsurprisingly, decreases in shaft stiffness led to more shaft bending at the transition from backswing to downswing (p < 0.001). Contrary to previous research, lead bending at impact marginally increased for the stiffer shaft (p = 0.003). Overall, and taking effect sizes into account, the changes in shaft stiffness in isolation did not have a meaningful effect on the measured parameters, for the type of shaft investigated.